A Recoverable Ruthenium Aqua Complex Supported on Silica Particles: An Efficient Epoxidation Catalyst. Issue 17 (22nd February 2017) - Ferrer, Íngrid; Fontrodona, Xavier; Roig, Anna; Rodríguez, Montserrat; Romero, Isabel
Abstract: The preparation and characterization of complexes with a phosphonated terpyridine (trpy) ligand (trpy‐P‐Et) and a bidentate pyridylpyrazole (pypz‐Me) ligand, with formula [Ru II (trpy‐P‐Et)(pypz‐Me)X] n + (2 : X=Cl, n =1;3 : X=H2 O, n =2), is described, together with the anchoring of3 on two types of supports: mesoporous silica particles (SP ) and silica‐coated magnetic particles (MSP ). Aqua complex3 is easily obtained by heating2 in refluxing water and exhibits a two‐electron Ru IV/II redox process. It was anchored onSP andMSP supports by two different synthetic strategies, yielding the heterogeneous systemsSP@3 andMSP@3, which were fully characterized by IR and UV/Vis spectroscopy, SEM, cyclic voltammetry, and differential pulse voltammetry. Catalytic olefin epoxidation was tested with molecular complex3 and itsSP@3 andMSP@3 heterogeneous counterparts, including reuse of the heterogeneous systems. TheMSP@3 material can be easily recovered by a magnet, which facilitates its reusability. Abstract : Support strategies : A molecular ruthenium aqua complex was anchored to mesoporous silica and silica‐coated magnetic particles by two synthetic strategies without significant modification of its coordination and electronic properties. The catalytic performance and the reutilization of these hybrid materials were explored in the epoxidation of alkenes (see figure).